2013
DOI: 10.1002/ps.3522
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic effects of herbicide-resistance genes on crop yield: a review

Abstract: The rapid adoption of genetically engineered herbicide-resistant crop varieties (HRCVs)-encompassing 83% of all GM crops and nearly 8% of the worldwide arable area-is due to technical efficiency and higher returns. Other herbicide-resistant varieties obtained from genetic resources and mutagenesis have also been successfully released. Although the benefit for weed control is the main criteria for choosing HRCVs, the pleiotropic costs of genes endowing resistance have rarely been investigated in crops. Here the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 87 publications
(166 reference statements)
1
26
0
Order By: Relevance
“…Adaptive resistance mutations in bacteria (Cohan, King, & Zawadzki, ; Melnyk, Wong, & Kassen, ), insects (Chevillon, Pasteur, Marquine, Heyse, & Raymond, ; Groeters, Tabashnik, Finson, & Johnson, ), and plants (Darmency, ; Vila‐Aiub et al, ) have been shown to incur resistance costs when they compromise normal function and metabolism (Uyenoyama, ). In particular, herbicide resistance point mutations may potentially trigger a number of biochemical changes at the herbicide target enzyme impairing enzyme catalytic capacity, reducing substrate affinity, and/or altering feedback inhibition, resulting in insufficient or excessive product biosynthesis and thus accounting for a resistance cost (Purrington & Bergelson, ; Vila‐Aiub et al, ; Vila‐Aiub, Yu, Han, & Powles, ; Yu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Adaptive resistance mutations in bacteria (Cohan, King, & Zawadzki, ; Melnyk, Wong, & Kassen, ), insects (Chevillon, Pasteur, Marquine, Heyse, & Raymond, ; Groeters, Tabashnik, Finson, & Johnson, ), and plants (Darmency, ; Vila‐Aiub et al, ) have been shown to incur resistance costs when they compromise normal function and metabolism (Uyenoyama, ). In particular, herbicide resistance point mutations may potentially trigger a number of biochemical changes at the herbicide target enzyme impairing enzyme catalytic capacity, reducing substrate affinity, and/or altering feedback inhibition, resulting in insufficient or excessive product biosynthesis and thus accounting for a resistance cost (Purrington & Bergelson, ; Vila‐Aiub et al, ; Vila‐Aiub, Yu, Han, & Powles, ; Yu et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A number of natural glyphosate‐resistant EPSPS variants have been found in microorganisms (Barry et al ., ; Funke et al ., ; Cui et al ., ; Yi et al ., ) and engineered into crop cultivars (Barry et al ., ; Green, ). The basis for the commercial release of crops carrying these EPSPS variants is an acceptable degree of glyphosate resistance without substantial negative effects on EPSPS catalytic activity and, consequently, on crop yield (Funke et al ., ; Darmency, ; Cui et al ., ; Yi et al ., ). Recent work on EPSPS gene synthetic shuffling has made it possible to introduce up to 21 mutations into a single plant EPSPS gene to achieve glyphosate‐resistant variants with near‐normal catalytic functionality (Dong et al ., ).…”
Section: Do Epsps Target‐site Glyphosate Resistance Mutations Lead Tomentioning
confidence: 99%
“…Thus, the Ser‐264‐Gly mutant allele endows resistance to triazine and certain other PSII‐inhibiting herbicides. It has been widely observed that plants with the resistance‐endowing Ser‐264‐Gly allele express a mean fitness cost of 25% (Gronwald, ; Bergelson & Purrington, ; Darmency, ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, resistance to synthetic auxins was associated with various pleiotropic effects on the growth and architecture of A. thaliana , without any change in time from sowing to emergence, perhaps because the study included laboratory but not field mutants. Little additional information can be found on pleiotropic effects in studies of herbicide‐tolerant crop varieties obtained by mutation because there are few comparative studies on isogenic cultivars, and we do know that lack of dormancy is an essential trait for crops, so breeding plans quickly eliminate any obstacle against quick and complete germination, if any …”
Section: Timing Of Emergence and Herbicide Resistance: Co‐selection mentioning
confidence: 99%
“…Little additional information can www.soci.org H Darmency, N Colbach, V Le Corre be found on pleiotropic effects in studies of herbicide-tolerant crop varieties obtained by mutation because there are few comparative studies on isogenic cultivars, and we do know that lack of dormancy is an essential trait for crops, so breeding plans quickly eliminate any obstacle against quick and complete germination, if any. 23…”
Section: Pleiotropymentioning
confidence: 99%